Mapping political ecology in Indonesia: A bibliometric analysis of trends, themes, and research gaps (1962–2025) - Iradhad Taqwa Sihidi; Salahudin Salahudin; Ach. Apriyanto Romadhan; Warda Kamelia; Hevi Kurnia Hardini (Education and Development Research, 2026)
The environmental crisis in Indonesia has developed into a complex structural problem involving power relations between the state, corporations, and communities in the management of natural resources. The political ecology approach provides a critical perspective that examines the social, political, and economic dimensions of these dynamics. Although political ecology studies on Indonesia are growing, bibliometric studies that map the knowledge structure, research networks, and thematic evolution in international literature are still limited. This gap means that there is no comprehensive picture of the direction of research and dominant themes in political ecology studies on Indonesia. This study aims to map the development of the literature on political ecology in Indonesia through a bibliometric approach based on the Scopus database for the period 1962–2025. The analysis uses VOSviewer and Bibliometrix (R Studio) software to reveal publication trends, knowledge structures, collaboration networks, and thematic evolution. The results show a significant increase in publications since 2010, with more than 60% of documents published in the period 2015–2025. The dominant keywords include governance, sustainability, and climate change, as well as issues of environmental justice and indigenous peoples. Thematic visualizations show a shift in studies from natural resource governance to progressive issues such as urban political ecology and feminist political ecology. These findings provide insight into the direction of political ecology research in Indonesia and can serve as a basis for determining research priorities on issues of environmental justice, resource conflicts, and the transformation of environmental governance towards greater inclusivity and sustainability.